Biodiesel Conversion from Used Cooking Oil: An Eggshell-Based ZnO/CaO Supported on Activated Carbon Catalyst with Microwave Heating - Ginting, Elfrida; Ginting, Amalia Anggreni; Simatupang, Lisnawaty; Sembiring, Jhony Hartanta; Ginting, Victor Eralingga (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Fossil fuels, such as petroleum, are non-renewable and have been exploited for decades, necessitating alternative energy solutions. Biodiesel reduces reliance on fossil fuels and mitigates their environmental impact. This research converts used cooking oil into biodiesel through chemical reactions—esterification and transesterification—that transform oils into biodiesel. Microwave heating accelerates reaction rates and reduces process times compared to conventional heating. A CaO catalyst derived from eggshells, impregnated with ZnO and supported by activated carbon, was chosen for its sustainability and enhanced catalytic activity. The study aims at determining the optimal conversion time for transforming used cooking oil into biodiesel according to SNI 7182-2015, using FT-IR and GC-MS analyses to assess chemical composition and purity. XRD and SAA confirmed the formation of CaO and a surface area of 3.822 m²/g. Microwave heating times of 4-8 minutes at 600 watts were tested, with the highest yield (89.62%) achieved in 5 minutes. This meets SNI 7182-2015 standards for density, kinematic viscosity, acid number, and saponification number. GC-MS identified cis-13-octadecenoic acid methyl ester (52.69%), pentadecanoic acid 14-methyl methyl ester (31.89%), and methyl stearate (6.14%) as the main components. These results demonstrate sustainable biodiesel production from waste cooking oil using environmentally friendly catalysts, reducing reliance on fossil fuels.